Handbook of human factors and ergonomics - Salvendy, Gavriel, 1938- (Wiley, 2012)
This is the fourth edition of the market-leading reference for human factors and ergonomics researchers, academics, and professionals. Editor Gavriel Salvendy, a well-known and respected authority, has assembled the top thinkers and practitioners from throughout the world to update this volume. It features new coverage of voice communication, multi-modal design, human-robot communication, call center design and operation, design of electronic games, and much more.Plus new and expanded coverage of Human Error and Human Reliability Analysis.